FORMULASI MASKER GEL PEEL OFF EKSTRAK BUNGA TELANG (Clitoria ternatea L.) SEBAGAI ANTIOKSIDAN ALAMI - Aulia Rahmi Azizah; Rasidah, Ananda Imroatur; Wilujeng, Firdianty Lestari; Piya, Nor; Yuliani, Siska Dwi; Adhila, Ghina; Sundu, Reksi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Natural ingredients containing antioxidant compounds can be made in the form of a peel-off gel mask which can help care for facial skin. Butterfly pea flowers (Clitoria ternatea L.) contain flavonoid anthocyanin compounds which can break the chain reaction of free radicals. The aim of this research is to determine the antioxidant activity of butterfly pea flower extract and the preparation of butterfly pea peel off gel mask. The peel off gel mask formulation uses butterfly pea flower extract with a concentration of 5%. Testing for antioxidant activity uses the DPPH method. Physical characteristics assessment includes organoleptic tests, homogeneity observations, spreadability tests, viscosity tests, drying time tests, and preparation pH tests. Based on the research results, the IC50 value of telang flower extract is 43.68 ppm in the very strong category and the IC50 value of the peel-off gel mask preparation is 307.71 ppm in the inactive category. This research shows that the ethanol extract of butterfly pea flowers has potential as a natural antioxidant.